Maternal and Neonatal Herpes Simplex Virus Infections - Pinninti, Swetha G.; Kimberlin, David W. (American Journal of Perinatology, 2013)
Genital herpes infections are extremely common worldwide and ∼22% of pregnant women are infected with herpes simplex virus. Eighty percent of those affected with genital herpes are unaware of being infected. The most devastating consequence of maternal genital herpes is neonatal herpes disease. Fortunately, neonatal herpes simplex infections are uncommon but due to the morbidity and mortality associated with the infection are often considered in the differential diagnosis of ill neonates. The use of polymerase chain reaction assay for diagnosis of central nervous system infections and the development of safe and effective antiviral therapy have revolutionized the diagnosis and management of these infants. Most recently, the initiation of long-term antiviral suppressive therapy in these infants has led to significant improvement in morbidity. This review will summarize the epidemiology of maternal and neonatal herpes infections and discuss clinical presentation, diagnosis, management, and follow-up of infants with neonatal herpes disease.
Keywords: genital herpes; neonatal herpes; acyclovir; PCR; antiviral therapy